The results of magnetic separation use in ore processing of metalliferous raw basalt of Volyn region - Malanchuk, Ye; Malanchuk, Z; Korniienko, V; Gromachenko, S (My University, 2016)
Purpose. To determine the effectiveness of the electric field use in ore processing for extraction of native copper concentrate from raw basalt, to identify the most technologically advanced grain-size classes of the feed stock. To define the nature of the relationship between the amount of recoverable concentrate and the main dominant factors – separator field density and the coarseness of the prepared raw material. Methods. We used the substantiated physical and chemical methods of elemental, mineral, fractional, particle size distribution analysis of the basalt rock mass under processing, methods of laboratory, semi-industrial and industrial research into crushing, grinding, classification, and electromagnetic separation processes at the stages of ore preparation of raw materials for the production of metalliferous industrial products. The methods of statistical modeling and experimental results regression analysis have been applied. Findings. The preferred grain-size classes in the process of ore preparation and classification of basalt rock components for electrostatic separation were determined. The dependences of copper concentrate production from basalt, tuff and lava-breccia on the electrostatic field density while changing grain-size classes in the initial product were worked out. The regression dependences of the copper concentrate output on various relationships between grain-size classes in the initial material and the electric field density were obtained. Originality. The content of native copper in basalt, lava breccia and tuff was established and the preferred grain-size classes in the process of ore preparation were identified. It is for the first time that the magnetic susceptibility of all three components of basalt raw material was determined, and the influence of the magnetic field on the output of titano-magnetite concentrate was shown as well as the rational grain size of ore preparation was detrmined. The dependences of the copper concentrate output have been established and the efficiency of the electrical separation in complex processing of basalt raw material has been proved.

Мета. Визначення ефективності використання електричного поля у процесі рудопідготовки для виділення концентрату самородної міді з базальтової сировини, встановлення найбільш технологічних класів крупності перероблюваної сировини й характеру залежності кількості добутого концентрату від основних домінуючих факторів – напруженості поля сепаратора та крупності підготовленої сировини. Методика. У роботі використані апробовані фізичні та хімічні методи аналізу елементного, мінерального, фракційного, гранулометричного складу переробки базальтової гірської маси, методи лабораторних, напівпромислових і промислових досліджень процесів дроблення, подрібнення, класифікації, електромагнітної сепарації на етапах рудопідготовки сировини до отримання металовмісних промпродуктів. Застосовані методи статистичного моделювання і регресійного аналізу результатів експериментальних досліджень. Результати. Встановлено класи крупності у процесі рудопідготовки і класифікації складових базальтової гірської маси до електросепарації. Виявлено залежності виходу мідного концентрату для базальту, туфу та лавобрекчії від напруженості електричного поля при варіюванні вмістом різних класів крупності у вихідному продукті. Отримано регресійні залежності виходу мідного концентрату від різних співвідношень між класами крупності у вихідному продукті та від напруженості електричного поля. Наукова новизна. Встановлено процентний вміст самородної міді у базальті, лавобрекчії, туфі та показані кращі класи крупності у процесі рудопідготовки. Вперше визначена магнітна сприйнятливість всіх трьох складових базальтової сировини, показано вплив величини магнітного поля на вихід концентрату титаномагнетиту й визначена раціональна крупність рудопідготовки. Вперше встановлено залежності виходу мідного концентрату й показана ефективність використання операції електричної сепарації при комплексній переробці базальтової сировини. Практична значимість. Отримані результати досліджень вказують на доцільність комплексної переробки базальтової сировини, і на цій основі розроблений спосіб її переробки.

Цель. Определение эффективности использования электрического поля в процессе рудоподготовки для выделения концентрата самородной меди из базальтового сырья, установление наиболее технологичных классов крупности перерабатываемого сырья и характера зависимости количества извлекаемого концентрата от основных доминирующих факторов – напряженности поля сепаратора и крупности подготовленного сырья. Методика. В работе использованы апробированные физические и химические методы анализа элементного, минерального, фракционного, гранулометрического состава перерабатываемой базальтовой горной массы, методы лабораторных, полупромышленных и промышленных исследований процессов дробления, измельчения, классификации, электромагнитной сепарации на этапах рудоподготовки сырья к получению металлосодержащих промпродуктов. Применены методы статистического моделирования и регрессионного анализа результатов экспериментальных исследований. Результаты. Установлены предпочтительные классы крупности в процессе рудоподготовки и классификации составляющих базальтовой горной массы к электросепарации. Установлены зависимости выхода медного концентрата для базальта, туфа и лавобрекчии от напряженности электрического поля при варьировании содержанием разных классов крупности в исходном продукте. Получены регрессионные зависимости выхода медного концентрата от различных соотношений между классами крупности в исходном продукте и от напряженности электрического поля. Научная новизна. Установлено процентное содержание самородной меди в базальте, лавобрекчии и туфе, а также показаны предпочтительные классы крупности в процессе рудоподготовки. Впервые установлена магнитная восприимчивость всех трех составляющих базальтового сырья, показано влияние величины магнитного поля на выход концентрата титаномагнетита и определена рациональная крупность рудоподго-товки. Впервые установлены зависимости выхода медного концентрата и показана эффективность использования операции электрической сепарации при комплексной переработке базальтового сырья. Практическая значимость. Полученные результаты исследований указывают на целесообразность комплексной переработки базальтового сырья, и на этой основе разработан способ его переработки.
Keywords: native copper; titano-magnetite; electrical separation; lava breccia; basalt; tuff